2015
DOI: 10.1002/bdra.23343
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‐1 promoter polymorphisms and risk of spina bifida

Abstract: Although, an association was not found between HO-1 polymorphisms and risk of spina bifida, we speculate that the combined effect of low HO-1 expression and exposures to known environmental oxidative stressors (low folate status or diabetes), may overwhelm antioxidant defenses and increase risk of NTDs and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, we carried out a case-control study with 300 Californian cohorts to investigate the association between two functional HMOX1 polymorphisms and this entity. In this study, although we observed a doubling in risk for the A allele in A(-413)T among non-Hispanic whites, we did not find an obvious risk association in the whole population [ 17 ].…”
Section: Other Perinatal Morbiditiesmentioning
confidence: 70%
See 2 more Smart Citations
“…Recently, we carried out a case-control study with 300 Californian cohorts to investigate the association between two functional HMOX1 polymorphisms and this entity. In this study, although we observed a doubling in risk for the A allele in A(-413)T among non-Hispanic whites, we did not find an obvious risk association in the whole population [ 17 ].…”
Section: Other Perinatal Morbiditiesmentioning
confidence: 70%
“…Spina bifida is a common congenital disorder characterized by abnormal closure of the embryonic neural tube. Its etiologies are multifactorial, including low maternal folate intake, maternal obesity, and maternal diabetes, each of which is associated with oxidative stress [ 17 ]. Since this etiology is also implicated in a strong genetic contribution, SNPs related to folate production or oxidative stress have been investigated.…”
Section: Other Perinatal Morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…HMOX1 genotyping of genomic DNA from patients in PE registry (HDP cohort) was carried out as follows: GTn genotypes were determined using PCR and fragment analyses, modified from a previous study [ 23 ]. Briefly, the GTn region was amplified by PCR using primer pairs with 5′ FAM (fluorescein)-labeled forward primer (F: 5′-6-FAM-AGAGCCTGCAGCTTCTCAGA-3′, R: 5′-ACAAAGTCTGGCCATAGGAC-3′), and the size of the labeled PCR product was determined by fragment analyses using ABI 3130 × Genetic Analyzer and Peakscanner (Thermo Fisher Cloud), with GeneScan-500ROX (Applied Biosystems) as a size marker.…”
Section: Methodsmentioning
confidence: 99%
“…A/T SNP (rs2071746) of patient samples was genotyped using TaqMan SNP genotyping assay (Cat 4351379, Applied Biosystems), 7900HT Real-Time PCR system, and TaqMan Genotyper software following the manufacturer’s instructions. Haploview 4.1 [ 24 ] was used to perform haplotype analyses, including accessing linkage disequilibrium and haplotype-HDP association analysis, with GTn variant being simplified as a SNP variant [ 23 ].…”
Section: Methodsmentioning
confidence: 99%